Pozycja prawna NNA w statutach polskich uczelni - Górak-Sosnowska, Katarzyna; Kostecki, Dawid (PRAWO i WIĘŹ, 2025)
This paper aims to analyse the legal status of non-academic staff (NAS) within the statutes of public academic institutions in Poland. Although they are formally part of the academic community, NAS are often marginalised in institutional practices and internal organisational regulations. The authors, using a formal-dogmatic method and quantitative-qualitative, examined 101 academic statutes of public universities. First, artificial intelligence tools were used to make a preliminary selection of the 20 most diverse statutes in terms of regulations concerning NNA. Next, using the MAXQDA tool, a qualitative analysis of the selected statutes was carried out in terms of: a) the place of NNA in the university community and their definition as a group of employees; b) the representation of NNA in university senates; c) representation in the electoral college; and d) other regulations. This paper contributes to debates on egalitarianism and the recognition of diverse professional roles within academia. The results of the analysis were used to formulate recommendations and proposals de lege ferenda.